The Effect of Suplemental Ascorbic Acid on the Development of Newcastle Disease in Japanese Quail (Coturnix coturnix Japonica) Exposed to High Ambient Temperature - Usman, B.A.; Mani, A.U.; El-Yuguda, A.D.; Diarra, S.S. (International Journal of Poultry Science, 2008)
In order to study the development of Newcastle Disease (ND) in Japanese quail subjected to high ambient temperature with or without supplementation with ascorbic acid (AA), eighty 3 week-old Japanese quails were randomly allotted to four equal groups. Two of the groups were kept at room temperature (26 ±0.5 °C) with one supplemented with AA (RA) and the other receiving no AA (RO). The other two groups were kept at a continuous temperature of 41.8 ±0.6 °C with one of them supplemented with AA (HA) and other receiving no AA (HO). The group RO served as the control. Ascorbic acid was supplemented at the rate of 1000mg/kg feed. Twelve birds in each of four groups were challenged oculonsally with a pigeon isolate of velogenic ND virus and the rest left as in contact. Morbidity rate was 100% in all challenged and in contact birds except in the incontact of the group supplemented with AA which recorded 50%. One hundred percent mortality was recorded in heat stressed groups irrespective of AA supplementation while 0% and 50% mortality was recorded in those kept at room temperature with or without AA supplementation respectively. None of the unchallenged in contact birds died in any of the groups. Lesions of ND in the experimentally infected quails were characterized by pathological lesions. The results of haemagglutination inhibition test performed on blood samples of all birds on days 0, 7, 14 and 21 post inoculations indicated no effect of heat treatment or AA supplementation on the humoral immune response of the Japanese quail. It was concluded that prolonged high ambient temperature has detrimental effects on the survival of Japanese quail with AA supplementation having some ameliorating effects. High ambient temperature may not adversely affect the humoral immune response of Japanese quail to Newcastle disease and AA may not be an important factor in the resistance of quails exposed to prolonged high ambient temperature to ND virus infection.